Penerapan Perlindungan Hukum Atas Produk Budaya Kekayaan Intelektual (KI) Golok Ciomas di Kecamatan Ciomas Kabupaten Serang - Sulasno Sulasno; Wahyuddin Wahyuddin; Fitria Agustin (LITERATUS, 2020)
Banten Province is famous for its historical, cultural and religious values, Banten province has various types of traditional weapons, one of which is a machete, a machete in ancient times used by champions to drive out invaders from their area. One of Banten's traditional weapons is the Ciomas Machete, which is located in the Ciomas Subdistrict of Serang Regency, this machete cannot be owned by just anyone, because even in the manufacturing process it is not arbitrary. An important principle that is also believed by the elders in Ciomas, which still holds strong the tradition of making the Ciomas Machete. This study aims to find out how the application of legal protection for the Ciomas Machete Brand in Ciomas District, Serang Regency. By using Descriptive Analytical Research Methods conducted by the method of data collection as well as by examining various sources of legal material, whether primary, secondary or tertiary. To implement and protect Ciomas Machete Marks from counterfeiting products or counterfeit goods or commonly known as "KW" goods, based on Law Number 20 Year 2016 Regarding Trademarks and Geographical Indications, regulated in Article 100 -Article 102 regarding criminal sanctions given to the counterfeiters of a product or goods, so it is hoped that the Ciomas Machete Brand will not falsify them for the benefit of a business.